PERBEDAAN TINGKAT KECEMASAN (ANXIETY) DALAM OLAHRAGA BERBASIS PERBEDAAN ETNIS (SUKU OSING, JAWA, DAN MADURA) - Moh Agung Setiabudi; Danang Ari Santoso (Universitas Sriwijaya, 2020)
In this modern era, sport is increasingly popular with Indonesian people. As sports develops, coaches continue to develop physical, technical, and psychological training models to achieve optimal performance in their built athletes. Psychology is one important aspect in sports. Many potential athletes fail because of psychological factors, namely mental. Anxiety factors (anxiety) possessed by individual athletes affect the appearance in the match. An athlete is an individual who has its own uniqueness, especially in a different tribe. He has his own talents, his own habits and his own culture and background that specifically affect him. Various differences that cause anxiety levels (anxiety) in sports will also not be the same. This type of research is a non-experimental quantitative research (ex post facto) with a survey approach. The samples in this study were the Osing, Javanese and Madurese using cluster sampling techniques. Respondents are athletes from the student volleyball team. The results showed that the anxiety level of Javanese and Madurese in the category of